Extortion Inland Waterway Routes: The Strategic Role of Local Communities in Achieving Sustainable Maritime Security - Edward Moshaddeq; Deasy Arisanty (Universitas Lambung Mangkurat, 2025)
This study examines illegal levies along the Sungai Putting–Taboneo inland waterway in South Kalimantan, Indonesia, focusing on the strategic role of local communities in promoting sustainable maritime security. Inland waterways are vital to trade in archipelagic nations like Indonesia but are often prone to organized crime, including extortion and collusion between criminal groups and corrupt officials. Using a qualitative descriptive approach, the study collected data between March and October 2024 through interviews with ship crews and local stakeholders. It mapped key sites and patterns of unofficial levies, revealing that both institutional and community actors demand payments, often in cash or barter (e.g., diesel fuel). The lack of standardized fees creates operational uncertainty and raises logistics costs. The findings show that repressive law enforcement alone is insufficient, as socio-economic vulnerabilities within local communities contribute to their involvement in extortion. As an alternative, the study recommends community empowerment through fishermen’s cooperatives, legal education, and participatory monitoring systems. These approaches, supported by global literature on community-based resource management, have proven effective in enhancing accountability and reducing illegal activity. The research is geographically limited to the Sungai Putting–Taboneo corridor and temporally to March–October 2024. While qualitative in nature and not broadly generalizable, the study contributes a micro-sociological perspective to maritime security, emphasizing the need for integrated, community-based solutions.